Lightweight medium-entropy alloy and preparation method and application thereof

Through the light medium-entropy alloy of Ti65-85%, Zr 2-12%, Nb 2-12%, V 4-12%, Al 5-15%, combined with vacuum magnetic levitation smelting technology, traditional alloys in aerospace environment have been solved. The problems of insufficient strength, density and thermal conductivity in the medium achieve low density, high strength and low thermal conductivity, which is suitable for extreme service environments.

CN119242985APending Publication Date: 2025-01-03DALIAN UNIV OF TECH +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411378714.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional light alloys have low strength, poor plasticity, high density and strong thermal conductivity in extreme service environments such as aerospace, and cannot meet the needs of low density and thermal management, resulting in an urgent need for lightweight, low thermal conductivity medium entropy alloys.

Method used

The light medium entropy alloys of Ti65-85%, Zr 2-12%, Nb 2-12%, V 4-12%, Al 5-15% are repeatedly melted and refined in a protective atmosphere by vacuum magnetic levitation smelting technology. Form an alloy with low thermal conductivity, high strength and high plasticity.

Benefits of technology

It realizes the low density, low thermal conductivity, high tensile strength, high hardness and high elongation of the alloy, which is suitable for extreme environments in the aerospace field and enhances the application prospects of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005069768500000011
    Figure HDA0005069768500000011
  • Figure HDA0005069768500000012
    Figure HDA0005069768500000012
  • Figure HDA0005069768500000013
    Figure HDA0005069768500000013
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy materials, and particularly relates to a light medium-entropy alloy and a preparation method and application thereof. According to the invention, common elements in a traditional medium-entropy alloy are abandoned, and low-density and low-thermal-conductivity elements are introduced, so that the light medium-entropy alloy with low thermal conductivity is obtained; according to the light medium-entropy alloy, the lattice distortion effect, the high-entropy effect, the hysteresis diffusion effect, the cocktail effect and other effects are adopted, and the strength and plasticity of the alloy are improved on the premise that the requirement for the light weight is met. The light medium-entropy alloy provided by the invention has the characteristics of light weight, low heat conductivity, high strength and high plasticity at room temperature, low density, high tensile strength, high hardness, high ductility and the like. Data of the embodiment show that the tensile strength of the light medium-entropy alloy is larger than or equal to 650 MPa, the percentage elongation after fracture is larger than or equal to 8%, the hardness is larger than or equal to 300 HV, and the heat conductivity is smaller than or equal to 10 W / m.K.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials, and in particular relates to a lightweight medium-entropy alloy and a preparation method and application thereof. Background Art

[0002] In recent years, research on lightweight materials has become increasingly in-depth. Traditional lightweight alloys, such as magnesium alloys, aluminum alloys or titanium alloys, have achieved many important research results due to their low density. However, traditional lightweight alloys have the disadvantages of low strength, poor plasticity and insufficient hardness, which limits their application in extreme service environments such as aerospace.

[0003] The introduction of medium-entropy alloys and their concept of medium-entropy has opened up new research areas for alloy materials and ways to optimize alloy properties. Traditional medium-entropy alloys have attracted widespread attention due to their excellent mechanical properties and numerous alloy systems. However, traditional medium-entropy alloys have high density and strong thermal conductivity, which cannot further meet the needs of low density and thermal management in aerospace and electronic products. The demand for lightweight and low thermal conductivity medium-entropy alloys is also more urgent.

[0004] How to further improve alloy plasticity, reduce alloy density, and at the same time meet low thermal conductivity requirements is a problem currently facing the field of lightweight medium-entropy alloys. Summary of the invention

[0005] The object of the present invention is to provide a lightweight medium-entropy alloy and a preparation method and application thereof. The lightweight medium-entropy alloy provided by the present invention has high strength, high plasticity and low thermal conductivity.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The invention provides a light medium entropy alloy, which comprises the following elements by mass percentage: Ti 65-85%, Zr 2-12%, Nb 2-12%, V 4-12%, and Al 5-15%.

[0008] Preferably, the lightweight medium entropy alloy comprises the following elements by mass percentage: Ti 70-80%, Zr 4-10%, Nb 4-8%, V 4-10%, and Al 5-10%.

[0009] The present invention also provides a method for preparing the lightweight medium entropy alloy described in the above scheme, comprising the following steps:

[0010] Part of Ti, Zr, V, Nb and the remaining Ti are placed in sequence from the bottom to the top of the copper crucible, Al is placed in a feeder, and then smelted, refined and cooled in a protective atmosphere in sequence, Al is added while smelting, and smelting, refining and cooling are repeated for more than 4 times. All of the Al is added during the first smelting to obtain the lightweight medium-entropy alloy.

[0011] Preferably, the purity of the Ti, Zr, V and Nb is above 99.95%; the particle size of the Ti is 3-5 mm; the particle size of the Zr is 3-15 mm; the particle size of the Nb is 3-6 mm; the particle size of the V is 3-5 mm; and the particle size of the Al is 20-50 mm.

[0012] Preferably, the mass ratio of the part of Ti to the remaining part of Ti is 2-3:1.

[0013] Preferably, the melting temperature is 1550-1750°C and the vacuum degree is 5×10 -3 ~7×10 -3 Pa, until all the metal raw materials are melted.

[0014] Preferably, the smelting equipment is a vacuum magnetic levitation smelting furnace; the power of the vacuum magnetic levitation smelting furnace is 253KW and the current is 520A.

[0015] Preferably, the refining temperature is 1600-1700° C., and the holding time is 4-6 minutes.

[0016] Preferably, the cooling is: reducing the power of the vacuum magnetic levitation smelting furnace and using circulating water for cooling; the power reduction rate is 50-60kW / min; the final temperature of the cooling is 20-25°C.

[0017] The present invention also provides the application of the lightweight medium-entropy alloy described in the above scheme or the lightweight medium-entropy alloy obtained by the preparation method described in the above scheme in the aerospace field.

[0018] The present invention provides a light medium-entropy alloy. Compared with traditional medium-entropy alloys, the present invention abandons the commonly used elements such as Co, Fe, Cr, Cu, Ni, etc. in traditional medium-entropy alloys, and obtains a light medium-entropy alloy with low thermal conductivity by introducing low-density elements (Ti, Al) and low thermal conductivity elements (Ti, Zr, V); compared with traditional light alloys, the light medium-entropy alloy provided by the present invention adopts lattice distortion effect, high entropy effect, hysteresis diffusion effect and cocktail effect, etc., to improve the strength and plasticity of the alloy under the premise of meeting the requirements of lightness.

[0019] The lightweight medium-entropy alloy provided by the present invention has both light weight and low thermal conductivity and high strength and high plasticity at room temperature, and has the characteristics of low density, low thermal conductivity, high tensile strength, high hardness and high elongation. The data of the embodiment show that the lightweight medium-entropy alloy provided by the present invention has a tensile strength of ≥650MPa, an elongation after fracture of ≥8%, a hardness of ≥300HV, and a thermal conductivity of ≤10W / m·K.

[0020] The present invention also provides a method for preparing the lightweight medium entropy alloy described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation, high feasibility and broad industrialization prospects.

[0021] Furthermore, the smelting equipment is a magnetic levitation smelting furnace; the power of the magnetic levitation smelting furnace is 253KW, and the current is 520A. The present invention adopts magnetic levitation smelting technology, which effectively avoids the contact between the molten metal and the crucible, and smelts without crucible material pollution, thereby ensuring the purity of the lightweight medium-entropy alloy.

[0022] The present invention also provides the application of the lightweight medium-entropy alloy described in the above scheme or the lightweight medium-entropy alloy obtained by the preparation method described in the above scheme in the field of aerospace. The lightweight medium-entropy alloy provided by the present invention has both light weight and low thermal conductivity and high strength and high plasticity at room temperature, and has the characteristics of low density, high tensile strength, high hardness and high elongation, etc. It is suitable for extreme service environments such as the field of aerospace, provides a guarantee for the application of the alloy, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 X-ray diffraction pattern of the Ti70Zr10Nb5V10Al5 alloy prepared in Example 1;

[0025] Figure 2 X-ray diffraction pattern of the Ti75Zr5Nb5V10Al5 alloy prepared in Example 2;

[0026] Figure 3 The X-ray diffraction pattern of the Ti80Zr4Nb4V4Al8 alloy prepared in Example 3;

[0027] Figure 4 The microstructure photograph of the Ti70Zr10Nb5V10Al5 alloy prepared in Example 1;

[0028] Figure 5The microstructure photograph of the Ti75Zr5Nb5V10Al5 alloy prepared in Example 2;

[0029] Figure 6 The microstructure photograph of the Ti80Zr4Nb4V4Al8 alloy prepared in Example 3;

[0030] Figure 7 is the stress-strain curve of the Ti70Zr10Nb5V10Al5 alloy prepared in Example 1;

[0031] Figure 8 is the stress-strain curve of the Ti75Zr5Nb5V10Al5 alloy prepared in Example 2;

[0032] Fig. 9 This is the stress-strain curve of the Ti80Zr4Nb4V4Al8 alloy prepared in Example 3. DETAILED DESCRIPTION

[0033] The invention provides a light medium entropy alloy, which comprises the following elements by mass percentage: Ti 65-85%, Zr 2-12%, Nb 2-12%, V 4-12%, and Al 5-15%.

[0034] Calculated by mass percentage, the lightweight medium entropy alloy provided by the present invention includes Ti 65-85%, preferably 68-82%, specifically 65%, 68%, 70%, 72%, 75%, 77%, 79%, 80%, 82% or 85%.

[0035] Calculated by mass percentage, the lightweight medium entropy alloy provided by the present invention includes Zr 2-12%, preferably 4-10%, specifically 2%, 4%, 5%, 6%, 7%, 8%, 10% or 12%.

[0036] Calculated by mass percentage, the lightweight medium entropy alloy provided by the present invention includes Nb 2-12%, preferably 4-8%, specifically 2%, 3%, 4%, 5%, 6%, 8%, 10% or 12%.

[0037] Calculated by mass percentage, the lightweight medium entropy alloy provided by the present invention includes V 4-12%, preferably 4-10%, specifically 4%, 5%, 6%, 8%, 9%, 10%, 11% or 12%.

[0038] Calculated by mass percentage, the lightweight medium entropy alloy provided by the present invention includes Al 5-15%, preferably 5-10%, specifically 5%, 6%, 7%, 8%, 9% or 10%.

[0039] The lightweight medium entropy alloy provided by the present invention has a density of 4.4 to 4.8 g / cm3 The entropy value is between 6.3 and 10.0 J / (mol·k). It has both light weight and low thermal conductivity as well as high strength and high plasticity at room temperature. It has the characteristics of low density, low thermal conductivity, high tensile strength, high hardness and high elongation, which provides a guarantee for the subsequent application of the alloy and has broad application prospects.

[0040] The present invention also provides a method for preparing the lightweight medium entropy alloy described in the above scheme, comprising the following steps:

[0041] Part of Ti, Zr, V, Nb and the remaining Ti are placed in sequence from the bottom to the top of the copper crucible, Al is placed in a feeder, and then smelted, refined and cooled in a protective atmosphere in sequence, Al is added while smelting, and smelting, refining and cooling are repeated for more than 4 times. All of the Al is added during the first smelting to obtain the lightweight medium-entropy alloy.

[0042] The present invention places part of Ti, Zr, V, Nb and the remaining part of Ti in sequence from the bottom to the top of the copper crucible, and places Al in the feeder. In the present invention, the copper crucible is preferably 6 kg grade.

[0043] In the present invention, the purity of the Ti, Zr, V and Nb is preferably above 99.95%, specifically 99.95%, 99.96%, 99.97%, 99.98% or 99.99%; the particle size of the Ti is preferably 3-5 mm, specifically 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm; the particle size of the Zr is preferably 3-15 mm, specifically 3 mm, 5 mm, 7 mm, 9 mm, 10 mm, 12 mm, 13 mm, 14 mm or 15 mm; the particle size of the Nb is preferably 3-6 mm, specifically 3 mm, 4 mm, 5 mm or 6 mm; the particle size of the V is preferably 3-5 mm, specifically 3 mm, 4 mm or 5 mm; the particle size of the Al is preferably 20-50 mm, specifically 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm or 50 mm.

[0044] In the present invention, the mass ratio of the part of Ti to the remaining part of Ti is preferably 2-3:1, and specifically may be 2:1.

[0045] After the raw materials are placed, the present invention sequentially melts, refines and cools in a protective atmosphere, adds Al while melting, repeats melting, refining and cooling, repeats for more than 4 times, and all the Al is added during the first melting to obtain the light medium entropy alloy. The present invention ensures the uniformity of the sample structure by repeated melting.

[0046] In the present invention, the protective atmosphere is preferably argon; the method for obtaining the protective atmosphere is preferably: evacuating the equipment through a three-stage pump body of a mechanical pump, a Roots pump and a diffusion pump, and when the vacuum degree of the equipment reaches 5×10 -3 ~7×10 -3 Pa, and then backwash the protective gas into the equipment.

[0047] In the present invention, the smelting temperature is preferably 1550-1750°C, specifically 1550°C, 1600°C, 1650°C, 1700°C or 1750°C, and the vacuum degree is preferably 5×10 -3 ~7×10 -3 Pa, specifically 5.5×10 -3 Pa or 6×10 -3 Pa, until the metal raw materials are completely melted, the holding time is preferably 4 to 6 minutes, specifically 5 minutes.

[0048] In the present invention, the smelting equipment is preferably a vacuum magnetic levitation smelting furnace; the power of the vacuum magnetic levitation smelting furnace is preferably 253KW, and the current is preferably 520A.

[0049] In the present invention, the refining temperature is preferably 1600-1700° C., specifically 1650° C., and the insulation time is preferably 4-6 min, specifically 4 min, 5 min or 6 min.

[0050] In the present invention, the refining equipment is preferably a vacuum magnetic levitation melting furnace; the power of the vacuum magnetic levitation melting furnace is preferably 253KW, and the current is preferably 520A.

[0051] In the present invention, the cooling is preferably: reducing the power of the vacuum magnetic levitation smelting furnace and using circulating water for cooling; the power reduction rate is preferably 50-60kW / min, specifically 55kW / min; the final temperature of the cooling is preferably 20-25°C, specifically 20°C, 22°C, 24°C or 24.5°C.

[0052] In the present invention, the number of repeated smelting, refining and cooling is preferably 4 to 6 times, specifically 4 times, 5 times or 6 times.

[0053] The present invention also provides the application of the lightweight medium-entropy alloy described in the above scheme or the lightweight medium-entropy alloy obtained by the preparation method described in the above scheme in the aerospace field.

[0054] The lightweight medium-entropy alloy provided by the present invention has both light weight and low thermal conductivity and high strength and high plasticity at room temperature. It has the characteristics of low density, low thermal conductivity, high tensile strength, high hardness and high elongation. It is suitable for extreme service environments such as the aerospace field, provides a guarantee for the application of the alloy, and has broad application prospects.

[0055] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0056] Example 1

[0057] The lightweight medium entropy alloy prepared in this embodiment has a chemical composition of Ti70Zr10Nb5V10Al5 according to the mass percentage, and the specific steps of the preparation method are as follows:

[0058] (1) Prepare raw materials Ti particles (3-5 mm, 99.99%), Zr particles (3-15 mm, 99.95%), Nb particles (3-6 mm, 99.95%), V particles (3×3 mm, 99.95%) and Al blocks (20-50 mm, 99.99%), and then place them in a 6 kg grade copper crucible. In view of the low density of the lightweight medium entropy alloy, the total weight of the raw materials is 3 kg.

[0059] (2) The position and order of placing raw materials: some Ti particles are placed on the bottom of the copper crucible, and then Zr particles are placed on top, and then Nb and V particles are placed (their positions are in the middle), and the remaining Ti particles are placed on the top layer. The Al block is placed in the feeder; the mass ratio of the partial Ti to the remaining Ti is 2:1.

[0060] (3) Before smelting, the circulating water is turned on, and then the three-stage pump body of the mechanical pump, Roots pump and diffusion pump is used to evacuate the chamber, and the vacuum degree is 5.5×10 -3 Pa, and then argon is backflushed into the furnace as a protective gas, and the final vacuum degree of the furnace body is maintained at 0.05Pa.

[0061] (4) The raw materials are melted by regulating the power and current. The power and current are slowly increased during the melting process, and the power is finally maintained at 253 kW and the current is 520 A. After all the metal is melted, the power is fixed for refining for 5 minutes, and then the power is gradually reduced and cooled.

[0062] (5) Repeat melting, refining and cooling in the crucible for 4 times, and finally turn off the power of the furnace and cool it in a water-cooled copper crucible to obtain a light medium-entropy alloy.

[0063] The performance of the lightweight medium entropy alloy was tested. First, the density was measured using the water displacement method, and the result was 4.72 g / cm 3Its thermal conductivity was tested by the German NETZSCH LFA-457 laser thermal conductivity tester, and the result was 5.43W / m·K; its hardness was measured by a Vickers hardness tester and was ≥320Hv.

[0064] XRD test was performed on the lightweight medium entropy alloy, and the results are as follows Figure 1 .according to Figure 1 From the XRD spectrum, an obvious BCC phase can be observed, and there is no obvious second phase diffraction peak.

[0065] Backscattering microscopy observation of lightweight medium entropy alloys shows the following results: Figure 4 As shown. Figure 4 Backscattered microstructure photographs further prove that it is mainly composed of BCC single phase.

[0066] The tensile test results of the lightweight medium entropy alloy are as follows Figure 7 As shown. Figure 7 From the tensile curve, it can be obtained that the tensile strength is ≥680MPa and the elongation after break is ≥10%.

[0067] Example 2

[0068] The lightweight medium entropy alloy prepared in this embodiment has a chemical composition of Ti75Zr5Nb5V10Al5 according to the mass percentage, and the specific steps of the preparation method are as follows:

[0069] (1) Prepare raw materials Ti particles (3-5 mm, 99.99%), Zr particles (3-15 mm, 99.95%), Nb particles (3-6 mm, 99.95%), V particles (3×3 mm, 99.95%) and Al blocks (20-50 mm, 99.99%), and then place them in a 6 kg copper crucible. Considering that the density of the lightweight medium-entropy alloy is further reduced compared to Example 1, the total weight of the raw materials is 3.1 kg.

[0070] (2) The position and order of placing raw materials: some Ti particles are placed on the bottom of the copper crucible, and then Zr particles are placed on top, and then Nb and V particles are placed (their positions are in the middle), and the remaining Ti particles are placed on the top layer. The Al block is placed in the feeder; the mass ratio of the partial Ti to the remaining Ti is 2:1.

[0071] (3) Before smelting, the circulating water is turned on, and then the three-stage pump body of the mechanical pump, Roots pump and diffusion pump is used to evacuate the chamber, and the vacuum degree is 5.5×10 -3 Pa, and then argon is backflushed into the furnace as a protective gas, and the final vacuum of the furnace body is maintained at 0.05Pa.

[0072] (4) The raw materials are melted by regulating the power and current. The power and current are slowly increased during the melting process, and the power is finally maintained at 253 kW and the current is 520 A. After all the metal is melted, the power is fixed for refining for 5 minutes, and then the power is gradually reduced and cooled.

[0073] (5) Repeat melting, refining and cooling in the crucible for 4 times, and finally turn off the power of the furnace and cool it in a water-cooled copper crucible to obtain a light medium-entropy alloy.

[0074] The properties of the lightweight medium entropy alloy were tested. First, the density was measured using the water displacement method, and the result was 4.65 g / cm 3 Its thermal conductivity was tested by the German NETZSCH LFA-457 laser thermal conductivity tester, and the result was 4.93W / m·K; its hardness was measured by a Vickers hardness tester and was ≥370Hv.

[0075] XRD test results of lightweight medium entropy alloys are as follows Figure 2 .according to Figure 2 From the XRD spectrum, an obvious BCC phase can be observed, and there is no obvious second phase diffraction peak.

[0076] Backscattering microscopy observation of lightweight medium entropy alloys shows the following results: Figure 5 As shown. Figure 5 Backscattered microstructure photographs further prove that it is mainly composed of BCC single phase.

[0077] The tensile test results of the lightweight medium entropy alloy are as follows Figure 8 As shown. Figure 8 From the tensile curve, it can be obtained that the tensile strength is ≥880MPa and the elongation after break is ≥10%.

[0078] Example 3

[0079] The lightweight medium entropy alloy prepared in this embodiment has a chemical composition of Ti80Zr4Nb4V4Al8 according to the mass percentage, and the specific steps of the preparation method are as follows:

[0080] (1) Prepare raw materials Ti particles (3-5 mm, 99.99%), Zr particles (3-15 mm, 99.95%), Nb particles (3-6 mm, 99.95%), V particles (3×3 mm, 99.95%) and Al blocks (20-50 mm, 99.99%), and then place them in a 6 kg copper crucible. Considering that the density of the lightweight medium-entropy alloy is further reduced compared to Example 1, the total weight of the raw materials is 3.3 kg.

[0081] (2) The position and order of placing raw materials: some Ti particles are placed on the bottom of the copper crucible, and then Zr particles are placed on top, and then Nb and V particles are placed (their positions are in the middle), and the remaining Ti particles are placed on the top layer. The Al block is placed in the feeder; the mass ratio of the partial Ti to the remaining Ti is 2:1.

[0082] (3) Before smelting, the circulating water is turned on, and then the three-stage pump body of the mechanical pump, Roots pump and diffusion pump is used to evacuate the chamber, and the vacuum degree is 5.5×10 -3 Pa, and then argon is backflushed into the furnace as a protective gas, and the final vacuum of the furnace body is maintained at 0.05Pa.

[0083] (4) The sample is melted by regulating the power and current. The power and current are slowly increased during the melting process, and the power is finally maintained at 253 kW and the current is 520 A. After the metal is completely melted, the power is fixed for refining for 5 minutes, and then the power is gradually reduced and cooled.

[0084] (5) Repeat melting, refining and cooling in the crucible for 4 times, and finally turn off the power of the furnace and cool it in a water-cooled copper crucible to obtain a light medium-entropy alloy.

[0085] The performance of the lightweight medium entropy alloy was tested. First, the density was measured using the water displacement method, and the result was 4.47 g / cm 3 Its thermal conductivity was tested by a German NETZSCH LFA-457 laser thermal conductivity tester, and the result was 4.72W / m·K; its hardness was measured by a Vickers hardness tester and was ≥325Hv.

[0086] XRD test was performed on the lightweight medium entropy alloy, and the results are as follows Figure 3 As shown. Figure 3 From the XRD spectrum, an obvious BCC phase can be observed. In addition to the Ti phase, the TiVAl phase can also be observed.

[0087] Backscattering microscopy observation of lightweight medium entropy alloys shows the following results: Figure 6 As shown. Figure 6 From the backscattered microstructure photograph, it can be seen that no obvious second phase can be observed at low magnification.

[0088] The tensile test results of the lightweight medium entropy alloy are as follows Fig. 9 As shown. Fig. 9 From the tensile curve, it can be obtained that the tensile strength is ≥650MPa and the elongation after break is ≥8%.

[0089] It can be seen from the above embodiments that the lightweight medium-entropy alloy provided by the present invention has both light weight and low thermal conductivity and high strength and high plasticity at room temperature, and has the characteristics of low density, low thermal conductivity, high tensile strength, high hardness and high elongation.

[0090] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A lightweight medium entropy alloy, characterized in that: Calculated by mass percentage, including the following elements: Ti 65~85%, Zr 2~12%, Nb 2~12%, V 4~12%, Al 5~15%.

2. The lightweight medium entropy alloy according to claim 1, characterized in that: The light medium entropy alloy includes the following elements by weight percentage: Ti 70~80%, Zr4~10%, Nb 4~8%, V 4~10%, Al 5~10%.

3. The method for preparing the lightweight medium entropy alloy according to any one of claims 1 to 2, characterized in that: The following steps are involved: Part of Ti, Zr, V, Nb and the remaining Ti are placed in sequence from the bottom to the top of the copper crucible, Al is placed in a feeder, and then smelted, refined and cooled in a protective atmosphere in sequence, Al is added while smelting, and smelting, refining and cooling are repeated for more than 4 times. All of the Al is added during the first smelting to obtain the lightweight medium-entropy alloy.

4. The preparation method according to claim 3, characterized in that: The purity of Ti, Zr, V and Nb is above 99.95%; The particle size of Ti is 3-5 mm; the particle size of Zr is 3-15 mm; the particle size of Nb is 3-6 mm; the particle size of V is 3-5 mm; and the particle size of Al is 20-50 mm.

5. The preparation method according to claim 3 or 4, characterized in that: The mass ratio of the part of Ti to the remaining part of Ti is 2-3:

1.

6. The preparation method according to claim 3, characterized in that: The smelting temperature is 1550-1750°C and the vacuum degree is 5×10 -3 ~7×10 -3 Pa, until all the metal raw materials are melted.

7. The preparation method according to claim 3 or 6, characterized in that: The smelting equipment is a vacuum magnetic levitation smelting furnace; the power of the vacuum magnetic levitation smelting furnace is 253KW and the current is 520A.

8. The preparation method according to claim 3, characterized in that: The refining temperature is 1600-1700° C., and the insulation time is 4-6 minutes.

9. The preparation method according to claim 3 or 8, characterized in that: The cooling is: reducing the power of the vacuum magnetic suspension melting furnace and cooling it with circulating water; The power reduction rate is 50-60 kW / min; the final cooling temperature is 20-25°C.

10. Application of the lightweight medium-entropy alloy according to any one of claims 1 to 2 or the lightweight medium-entropy alloy obtained by the preparation method according to any one of claims 3 to 9 in the field of aerospace.

Citation Information

Patent Citations

  • Light super-tough and high-strength NbTiVAlxZry as-cast high-entropy alloy

    CN110669977A

  • Low-density high-strength high-plasticity high-entropy alloy material and preparation method thereof

    CN111549270A

  • Ti-V-Zr-Nb-Al-Ta-Hf series light high-strength high-entropy alloy and preparation method thereof

    CN115233072A

  • Light high-temperature alloy with low expansion coefficient and preparation method thereof

    CN115287518A

  • Lightweight refractory high-entropy alloy and preparation method and application thereof

    CN118345296A